2011
DOI: 10.1007/s00213-011-2494-y
|View full text |Cite
|
Sign up to set email alerts
|

The bed nucleus of stria terminalis and the amygdala as targets of antenatal glucocorticoids: implications for fear and anxiety responses

Abstract: Altogether, our results show that in utero DEX exposure can modulate anxiety and fear behavior in parallel with significant morphological, neurochemical and molecular changes; importantly, GCs seem to differentially affect distinct brain regions involved in this type of behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 75 publications
5
27
1
Order By: Relevance
“…One other interesting finding supported by this work and our previous studies 12,13 was the selectivity of DA receptor D2 expression changes (putatively due to epigenetic alterations 13 ) in the mesocorticolimbic system, particularly in the light of evidence associating D2 receptor with reward-associated disorders that present altered incentive salience attribution such as addiction and binge eating 60 as well as motivation perception. 61 Moreover, it was shown that the D2 antagonist pimozide abolishes PIT, 17 and NAc microinjections of D2 antagonist raclopride reduce transfer.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…One other interesting finding supported by this work and our previous studies 12,13 was the selectivity of DA receptor D2 expression changes (putatively due to epigenetic alterations 13 ) in the mesocorticolimbic system, particularly in the light of evidence associating D2 receptor with reward-associated disorders that present altered incentive salience attribution such as addiction and binge eating 60 as well as motivation perception. 61 Moreover, it was shown that the D2 antagonist pimozide abolishes PIT, 17 and NAc microinjections of D2 antagonist raclopride reduce transfer.…”
Section: Discussionsupporting
confidence: 79%
“…D2 receptor (~47 kDa isoform) was increased in the mPFC (Figures 3c and d; U =0.0, P =0.01) and in the OFC (Figures 3g and h; U =0.0, P =0.004) of iuGC animals; these findings are in alignment with those previously reported for the NAc 13 and amygdala. 12 Conversely, we did not find changes in the D1 or D3 receptors in both the mPFC (Figures 3c and d) and the OFC (Figures 3g and h). …”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…In addition, deficits in learning and memory, and increased anxiety, have been observed in such instances (Hauser et al, 2009). Accompanying such behavioral alterations are structural changes in brain regions including the hippocampus, amygdala, and bed nucleus of the stria terminalis, that are known to be involved in learning, memory, anxiety, and stress responsiveness (Noorlander et al, 2008;Oliveira et al, 2012;Zuloaga et al, 2012). Complementing these studies with glucocorticoid exposure are others that subjected pregnant rats to environmental stressors at different points in gestation.…”
Section: Influence Of Environment In Utero On Biology Of Future Genermentioning
confidence: 99%
“…1 Currently used therapeutic regimens have important limitations such as long-time lag for clinical response, induction of resistance or even response failure. 2, 3 Several different factors seem to have a role in MD: imbalances in neurotransmitters 4 and cytokine production, 5, 6 hypothalamic–pituitary–adrenal axis dysregulation 7 and impaired neuroplasticity. 8, 9 …”
Section: Introductionmentioning
confidence: 99%